THE ROLE OF JOINT VENTURES IN THE DEVELOPMENT OF INVESTMENT AND EXPORT ACTIVITIES OF UZBEKISTAN (The Conference Hub, 2025)
This thesis substantiates the role of joint ventures in the development of investment and export activities of our republic.Direct cooperation between enterprises is considered a form of direct economic relations. Its distinctive features include: such activities are carried out between enterprises without state intervention; efficient use of resources and economic potential based on cooperation; cooperation enhances the export potential of enterprises and increases foreign currency revenues; moreover, it is evaluated not only by the delivery of finished products to consumers, but also by the supply of components at a technical level.